Phenomena in Romance verb paradigms: Syncretism, order of inflectional morphemes and thematic vowel - Baldi, Benedetta; Savoia, Leonardo M. (LingBaW. Linguistics Beyond and Within, 2022)
This article aims to propose a treatment of the internal morphological organization of words, based on the idea that morphology is part of syntactic computation. We disagree with Distributed Morphology model, whereby morphology is identified with a post-syntactic component conveying an information ‘separated from the original locus of that information in the phrase marker’ (Embick and Noyer 2001: 557) by rules manipulating syntactic nodes. We also consider inadequate the costly and complex syntactic structures that cartographic approach maps into inflectional strings. We pursue a different conceptualization assuming that morphology is governed by the same rules and principles of syntax. Sub-word elements, including inflections, thematic exponents and clitics, are fully interpretable and enter (pair-)merge operations (in the sense of Chomsky 2020a,b, 2021) according to their content, giving rise to complex words.